A DSP-based regular sampled pulsewidth modulation (PWM) technique for a multilevel inverter - Ahmad Azli, Naziha (IEEE, 2004)
Implementation of a regular sampled PWM technique based on a single carrier multilevel modulation strategy on a multilevel inverter using a digital signal processor (DSP) is presented in this paper. The equations representing the leading edges of the PWM pulses for the multilevel inverter are utilized in generating the gating signals for the multilevel inverter power devices using a dSPACE DS1102 controller board. Two types of the DS1102 controller board implementation are presented. The first type involves the development of Matlab/Simulink blocks that models a PWM signal generator and used in conjunction with Matlab/real-time workshop and dSPACE/real-time interface to actually generate the signals. The other type involves hand-coding (writing of a C program) with algorithms designed to generate PWM signals using the DS1102 controller board. Results based on both types of the DS1102 controller board implementation are compared and analysed. The performance of the multilevel inverter employing the later is also evaluated in terms of its output voltage waveforms and harmonic spectrums with variations in the modulation index.